Routledge international handbook of green criminology - Brisman, Avi; South, Nigel (Routledge international handbooks, 2013)
"Academic and general interest in environmental crimes, harms, and threats, as well as in environmental legislation and regulation, has grown sharply in recent years. The Routledge International Handbook of Green Criminology is the most in-depth and comprehensive volume on these issues to date. With contributions from leading international green criminologists and scholars in related fields, the Handbook examines a wide range of substantive issues, including: climate change ; corporate criminality and impacts on the environment ; environmental justice ; media representations ; pollution (e.g. air, water) ; questions of responsibility and risk ; wildlife trafficking. The chapters explore green criminology in depth, its theory, history and development, as well as methodological concerns for this area of academic interest. With examples of environmental crimes, harms, and threats from Africa, Asia, Australia, Eastern Europe, South America, the United Kingdom, and the United States, this book will serve as a vital resource for international scholars and students in criminology, sociology, law and socio-legal studies, as well as environmental science, environmental studies, politics and international relations."--Publisher's website